For their own good: Recruiting children for research - Campbell, Alan (2008)
This article arose from the author's experiences as a researcher exploring children's reactions to their parents' separation. Between 1999 and 2004, the author undertook to find out what a sample of Australian children thought of their abilities to participate in decisions that directly affected them following family breakdown. Before beginning the project, the author was required to obtain ethical approval from the university to which he was attached at that time. He also talked with a number of service providers in Adelaide, where he was based, to request that he receive referrals from them once the research was under way. This article describes the difficulties the author experienced in obtaining ethical approval and subsequently in recruiting children for the research. The article reflects on these difficulties and presents a rationale for considering the participation of children in research about them. Copyright © 2008 SAGE Publications.